Multimodal Imaging of Integrin Receptor-Positive Tumors by Bioluminescence, Fluorescence, Gamma Scintigraphy, and Single-Photon Emission Computed Tomography Using a Cyclic RGD Peptide Labeled with a Near-Infrared Fluorescent Dye and a Radionuclide - W. Barry Edwards; Walter J. Akers; Yunpeng Ye; Philip P. Cheney; Sharon Bloch; Baogang Xu; Richard Laforest; Samuel Achilefu (Molecular Imaging)
Integrins, particularly the α v β 3 heterodimers, play important roles in tumor-induced angiogenesis and invasiveness. To image the expression pattern of the α v β 3 integrin in tumors through a multimodality imaging paradigm, we prepared a cyclic RGDyK peptide analogue (LS308) bearing a tetraazamacrocycle 1,4,7,10-tetraazacyclododecane- N, N′, N″, N‴ -tetraacetic acid (DOTA) and a lipophilic near-infrared (NIR) fluorescent dye cypate. The α v β 3 integrin binding affinity and the internalization properties of LS308 mediated by the α v β 3 integrin in 4t1 luc cells were investigated by receptor binding assay and fluorescence microscopy, respectively. The in vivo distribution of 111 In-labeled LS308 in a 4t1 luc tumor-bearing mouse model was studied by fluorescence, bioluminescence, planar gamma, and single-photon emission computed tomography (SPECT). The results show that LS308 has high affinity for α v β 3 integrin and internalized preferentially via the α v β 3 integrin-mediated endocytosis in 4t1 luc cells. We also found that LS308 selectively accumulated in α v β 3 -positve tumors in a receptor-specific manner and was visualized by the four imaging methods. Whereas the endogenous bioluminescence imaging identified the ensemble of the tumor tissue, the fluorescence and SPECT methods with the exogenous contrast agent LS308 reported the local expression of α v β 3 integrin. Thus, the multimodal imaging approach could provide important complementary diagnostic information for monitoring the efficacy of new antiangiogenic drugs.